2012
DOI: 10.1123/jpah.9.4.554
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Evidence of the Physical Activity Transition in Kenya

Abstract: Background:Comparable data to examine the physical activity (PA) transition in African countries such as Kenya are lacking.Methods:We assessed PA levels from urban (UKEN) and rural (RKEN) environments to examine any evidence of a PA transition. Nine- to twelve-year-old children participated in the study: n = 96 and n = 73 children from UKEN and RKEN, respectively. Pedometers were used to estimate children’s daily step count. Parental perception regarding their child’s PA patterns was collected via questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
76
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(86 citation statements)
references
References 28 publications
9
76
0
Order By: Relevance
“…A comparison between these rural 9-11-year-old South African children (predominantly Caucasian children) and 9-12-year-old children from rural Kenya (only black African children), also indicated that the rural Kenyan children are more active than this study group (14 700 +/-521 versus 11 601 +/-2 454). 13 This trend is supported by Craig et al; they reported high activity volume Canadian children in the same age groups (CANPLAY) (Figure 2). 9 This study, the largest and most comprehensive set of sex-and age-specific normative reference data for children's and adolescents' pedometer-determined physical activity to date, was done between 2005 and 2011 on 21 271 children (5-12 years) and 12 956 adolescents (13-19 years) and correlates with other international reference literature on the normative values for physical activity.…”
supporting
confidence: 75%
“…A comparison between these rural 9-11-year-old South African children (predominantly Caucasian children) and 9-12-year-old children from rural Kenya (only black African children), also indicated that the rural Kenyan children are more active than this study group (14 700 +/-521 versus 11 601 +/-2 454). 13 This trend is supported by Craig et al; they reported high activity volume Canadian children in the same age groups (CANPLAY) (Figure 2). 9 This study, the largest and most comprehensive set of sex-and age-specific normative reference data for children's and adolescents' pedometer-determined physical activity to date, was done between 2005 and 2011 on 21 271 children (5-12 years) and 12 956 adolescents (13-19 years) and correlates with other international reference literature on the normative values for physical activity.…”
supporting
confidence: 75%
“…[92][93][94][95][96][97][98][99][100] Generational declines in active transportation 101,102 and independent mobility 103 have also been observed. These trends are consistent with the increased fear of the outdoors and a convenience lifestyle.…”
Section: Successes and Challenges Based On Indicator Gradesmentioning
confidence: 99%
“…107 Temptations for sedentary behaviors are increasing as the world becomes increasingly cyber-centric, auto-dependent, and urbanized, consistent with epidemiological and physical activity transitions. 18,19,101 Self-report sedentary behavior data on representative samples of children and youth from 42 countries revealed that 62% and 63% of 13-and 15-year-olds, respectively, watched ≥2 hours of television per day on weekdays. 7 Despite evidence that television viewing time in some countries may be decreasing among children, other sedentary screen time use (eg, computers, tablets, smartphones, electronic games) has more than compensated for this decline.…”
Section: Successes and Challenges Based On Indicator Gradesmentioning
confidence: 99%
See 1 more Smart Citation
“…[11] Life in an urban setting has a severe negative impact on the amount of physical activity a child has the chance to enjoy. [12] In urban and periurban regions, safety concerns contribute to the decrease in physical activity, [11] e.g. it is no longer safe for children to walk to school or to play in parks.…”
mentioning
confidence: 99%